(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The process of delivering food from restaurants via the Internet is known as online food delivery. It is used by applications such as Grab Food and Food Panda or other third-party food delivery apps that can see the promos released by the store, and it can be delivered. Online food delivery provides a service that leads to satisfied customers in terms of delivery time, food quality, promotions, discounts, and so on. The purpose of this research is to find out if the customers are satisfied with the online food delivery services at Novaliches Quezon City of the chosen provider by the researcher, who is Grabfood, Foodpanda, and other third-party food delivery applications. The results of this study reveal that the total level of customer satisfaction with online food delivery evaluated as the majority are “satisfied” in terms of friendly user app, time of delivery, the behavior of delivery, freebies/promos, mode of payment, plenty to choose to menu, and discount; but there is one variable that came out in the result “dissatisfied” it is the quality of products, more customers experienced the packaging is not good condition, the product is already messed up, misassembled product and last wrong item when delivered. The study’s findings show that one of the most common problems encountered by online food delivery is long delivery time. With the frequency of 66 over 100 respondents, the respondents are mostly waiting for a long delivery time. The researchers recommended that the mobile application for food delivery must have a clear procedure, especially for its new users. Furthermore, delivery riders must give more information about the condition of the product and inform the customer about the delivery period to avoid cancellation and complaints. The researchers also recommend practicing various interactions, learning better communication, improving problem-solving skills, and transforming into better people when dealing with customers.